High-tap-density iron phosphate battery precursor

Through acid leach dissolution and step-by-step adjustment of pH value, combined with the introduction of polyethylene glycol, the problem of poor uniformity of iron phosphate particles is solved, and the precursor of iron phosphate battery with high tap density and large specific surface area is realized, which improves the compaction performance of lithium iron phosphate.

CN119612472APending Publication Date: 2025-03-14SICHUAN LIYUAN NEW MATERIALS CO LTD +1
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510047874.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The micromorphic agglomeration of iron phosphate prepared by the existing ammonium process is severely agglomerated and poor particle uniformity, resulting in a low tap density and reducing the energy density of the finished lithium iron phosphate.

Method used

By acid leaching and dissolving alkaline ammonium ferric phosphate, and using step-by-step adjustment of the system pH value and introducing polyethylene glycol, we promote iron phosphate nucleus crystallization and particle agglomeration, and improve tap density and specific surface area.

Benefits of technology

The iron phosphate battery precursor with high tap density and large specific surface area is achieved, and the compaction performance of lithium iron phosphate is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119612472A_ABST
    Figure CN119612472A_ABST
Patent Text Reader

Abstract

The invention discloses a high-tap-density iron phosphate battery precursor which is prepared by the following steps: dispersing a basic ammonium iron phosphate filter cake into an acid solution with the pH value of 0.4-0.6, stirring until the filter cake is completely dissolved, adding an alkali solution to adjust the pH value of a base solution to 0.8-1.2, and adding polyethylene glycol for reaction; after the reaction is finished, alkali liquor continues to be added into the solution to adjust the pH value to 1.8-2.2, the temperature is increased to the aging temperature, iron phosphate dihydrate slurry is prepared, and finally the anhydrous iron phosphate with the high tap density is prepared after suction filtration, water washing, drying and calcination are conducted. According to the iron phosphate battery precursor disclosed by the invention, basic ammonium iron phosphate is firstly subjected to acid leaching and then subjected to recombination crystallization during preparation, the pH value of a system is adjusted step by step, and polyethylene glycol is introduced, so that the tap density is improved, the iron phosphate battery precursor has a large specific surface area, large and small particle grading is formed, and the compaction performance of lithium iron phosphate is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of preparation of lithium iron phosphate positive electrode materials, and in particular relates to a high-tap iron phosphate battery precursor. Background Art

[0002] With the development of technology, lithium-ion batteries have become the most popular power batteries. Among them, lithium iron phosphate batteries are widely used in the field of electric vehicles due to their advantages such as high energy density, long cycle life and good safety performance.

[0003] The preparation processes of positive electrode materials for lithium-ion batteries mainly include: solid phase method, complex method, dissolution-gel method, plasma exchange method, spray drying method, high temperature solid phase synthesis method, carbon thermal reduction method and microwave drying technology, etc. Among them, the method more suitable for industrialization is the high temperature solid phase synthesis method, that is, lithium carbonate, lithium hydroxide, etc. are used as lithium sources, ferrous oxalate, ferrous oxalate, iron oxide, iron phosphate, etc. are used as iron sources, and they are mixed and sintered at high temperature.

[0004] Studies have shown that the performance of lithium iron phosphate is directly affected by the various parameters of the raw material iron phosphate. However, the iron phosphate prepared by the current ammonium process has serious microscopic agglomeration and poor particle uniformity, resulting in a generally low tap density, which greatly reduces the energy density of the finished lithium iron phosphate.

[0005] Therefore, there is an urgent need to develop an iron phosphate positive electrode material with high tap density and large specific surface area. Summary of the invention

[0006] Purpose of the invention: The technical problem to be solved by the present invention is to provide an iron phosphate battery precursor with high tap density and large specific surface area.

[0007] Technical solution: The high-tap iron phosphate battery precursor of the present invention is prepared by the following steps:

[0008] (1) Dispersing the basic ammonium ferric phosphate filter cake in an acid solution with a pH value of 0.4 to 0.6, stirring for 30 to 60 minutes until the filter cake is completely dissolved, adding alkali solution to adjust the pH value of the base solution to 0.8 to 1.2, and adding polyethylene glycol, and reacting at 40 to 60° C. for 1 to 2 hours;

[0009] (2) adding alkali solution to the solution after the reaction in step (1) to adjust the pH value to 1.8-2.2, raising the temperature to the aging temperature, and aging for 3-6 hours to obtain ferric phosphate dihydrate slurry;

[0010] (3) The dihydrate iron phosphate slurry is filtered, washed, dried, and calcined to obtain anhydrous iron phosphate with high tap density.

[0011] The present invention is based on the preparation of anhydrous ferric phosphate with basic ammonium ferric phosphate. After the prepared basic ammonium ferric phosphate is dissolved by acid leaching, the pH value of the base solution after acid leaching is adjusted in steps with alkali solution. Since the nucleation rate of ferric phosphate is higher and the fine crystal growth rate is faster under low pH conditions, the pH value of the base solution is first adjusted to the range of 0.8 to 1.2, and the nucleation and crystallization of ferric phosphate are promoted under the condition of the base solution with a lower pH range. At this time, PEG is introduced. The high concentration of PEG can adhere to the surface of ferric phosphate grains and act as a binder, thereby promoting the agglomeration of primary particles of ferric phosphate, increasing the tap density and increasing the particle size. Due to the presence of ammonium ions in the recrystallization process and the lower pH of the base solution, the ferric phosphate grains are refined, so that it can also have a larger specific surface area.

[0012] Subsequently, another portion of alkali solution is added to increase the pH of the base solution to 1.8-2.2. Under higher pH conditions, the nucleation rate and growth rate of iron phosphate decrease, and at the same time, the concentrations of phosphate and iron ions in the base solution decrease, thereby reducing the particle size of iron phosphate. As the reaction proceeds, the concentration of PEG in the base solution decreases. The lower concentration of PEG can promote the dispersion between iron phosphate grains, prevent the aggregation and growth of iron phosphate particles, and eventually form a gradation of large and small particles, thereby increasing the tap density of iron phosphate and the compacted density of lithium iron phosphate.

[0013] Furthermore, in the step (1) of preparing the iron phosphate battery precursor of the present invention, the amount of polyethylene glycol added is 0.2-1% of the theoretical output mass of iron phosphate.

[0014] Furthermore, in the step (2) of preparing the iron phosphate battery precursor of the present invention, the alkali solution is added for 30 to 60 minutes, and the aging temperature is 75 to 90°C.

[0015] Furthermore, in the preparation step (1) of the iron phosphate battery precursor of the present invention, the basic ammonium ferric phosphate filter cake is prepared by the following steps: preparing a ferrous salt solution, a phosphate salt solution, and an oxidant solution, mixing and stirring, and obtaining a basic ammonium ferric phosphate filter cake after suction filtration and water washing; wherein the molar ratio of ferrous salt to phosphate salt is (1 to 1.15):1, and the molar ratio of ferrous salt to oxidant is 1:(0.5 to 0.8).

[0016] Furthermore, the iron concentration of the ferrous salt solution used in the basic ammonium ferric phosphate filter cake of the present invention is 55-58 g / L, and the ferrous salt is ferrous sulfate and / or ferrous chloride.

[0017] Furthermore, the phosphorus concentration of the phosphate solution used in the basic ammonium ferric phosphate filter cake of the present invention is 65-68 g / L, the phosphate salt is monoammonium phosphate and / or diammonium phosphate; and the oxidant is hydrogen peroxide and / or sodium peroxide.

[0018] Furthermore, the acid solution used in the basic ammonium ferric phosphate filter cake of the present invention includes at least one of phosphoric acid, sulfuric acid or hydrochloric acid; the alkali solution includes at least one of sodium hydroxide, sodium carbonate or sodium bicarbonate.

[0019] Furthermore, in step (3) of preparing the iron phosphate battery precursor of the present invention, the mass ratio of dihydrate iron phosphate to pure water during the filtration and washing is 1:(15-25); the drying temperature is 90-120°C, and the drying time is 8-12h; the calcination temperature is 450-600°C, and the calcination time is 2-4h.

[0020] Beneficial effect: Compared with the prior art, the significant advantages of the present invention are: the iron phosphate battery precursor prepared by the present invention is prepared by first acid-leaching the basic ammonium ferric phosphate, then reorganizing the crystallization, and adjusting the system pH in steps and introducing polyethylene glycol, thereby not only improving the tap density, but also having a large specific surface area, and forming a large and small particle gradation, thereby improving the compaction performance of lithium iron phosphate. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is a SEM image of the iron phosphate battery precursor prepared in Example 1 of the present invention;

[0022] Figure 2 This is a SEM image of the iron phosphate battery precursor prepared in Example 2 of the present invention;

[0023] Figure 3 This is a particle size diagram of the iron phosphate battery precursor prepared in Example 1 of the present invention;

[0024] Figure 4 This is a SEM image of the iron phosphate battery precursor prepared in Comparative Example 1 of the present invention. DETAILED DESCRIPTION

[0025] The technical solution of the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments.

[0026] It should be noted that the raw materials used in the present invention can all be purchased from commercial sources.

[0027] Example 1

[0028] The high-tap iron phosphate battery precursor of Example 1 is prepared by the following steps:

[0029] (1) Preparation of basic ferric phosphate: prepare 5.29 L of ferrous sulfate solution with an iron concentration of 56 g / L, 2.71 L of monoammonium phosphate solution with a phosphorus concentration of 67 g / L, and 10% hydrogen peroxide; then start the reactor for stirring and heating (the reactor speed is 120 rad / min, the temperature is 45° C.), pour the ferrous sulfate solution and the monoammonium phosphate solution into the reactor in sequence as the base liquid, and use a peristaltic pump to drop hydrogen peroxide into the base liquid (dropping rate is 15 mL / min); after the dropwise addition is completed, the temperature is raised to 70° C., mixed and stirred for 3 h, and filtered and washed with water to obtain a basic ammonium ferric phosphate filter cake; wherein the molar ratio of ferrous sulfate to monoammonium phosphate is 1.1:1, and the molar ratio of ferrous sulfate to hydrogen peroxide is 1:0.6.

[0030] (2) The prepared basic ammonium ferric phosphate filter cake was dispersed in a phosphoric acid solution with a pH value of 0.4 and stirred for 30 min until the slurry was dissolved. Then, the pH of the system was adjusted to 1.0 with a sodium hydroxide solution, and polyethylene glycol with a theoretical output weight of 0.8% of the ferric phosphate was added. The temperature was raised to 55° C. and the reaction was carried out for 1 h.

[0031] (3) Continue to add sodium hydroxide solution to the solution after the aging reaction in step (2) to adjust the pH value to 1.8, raise the temperature to 85° C., and age for 4 hours to obtain dihydrate ferric phosphate slurry; the sodium hydroxide solution is added for 40 minutes.

[0032] (4) The prepared ferric phosphate dihydrate slurry is filtered and washed with pure water at a mass ratio of 1:25 to obtain a ferric phosphate dihydrate filter cake; the filter cake is then transferred to a forced air drying oven and dried at 110°C for 12 hours to obtain ferric phosphate dihydrate; the filter cake is then loaded into an alumina sagger and sent to a high-temperature box furnace, and sintered at 550°C for 2 hours to obtain anhydrous ferric phosphate.

[0033] Example 2

[0034] The high-tap iron phosphate battery precursor of Example 2 is prepared by the following steps:

[0035] (1) Preparation of basic ferric phosphate: prepare 5.29 L of ferrous chloride solution with an iron concentration of 55 g / L, 2.71 L of diammonium phosphate solution with a phosphorus concentration of 65 g / L, and sodium peroxide with a concentration of 4%; then start the reactor to stir and heat (the reactor speed is 150 rad / min, the temperature is 40°C), pour the ferrous chloride solution and diammonium phosphate solution into the reactor in turn as the base liquid, and use a peristaltic pump to drop hydrogen peroxide into the base liquid (dropping rate is 15 mL / min); after the dropwise addition is completed, the temperature is raised to 65°C, mixed and stirred for 4 hours, and filtered and washed with water to obtain a basic ammonium ferric phosphate filter cake; wherein the molar ratio of ferrous sulfate to monoammonium phosphate is 1:1, and the molar ratio of ferrous sulfate to sodium peroxide is 1:0.5.

[0036] (2) The prepared basic ammonium ferric phosphate filter cake was dispersed in a sulfuric acid solution with a pH value of 0.5 and stirred for 50 min until the slurry was dissolved. Then, the pH of the system was adjusted to 0.8 with a sodium carbonate solution, and polyethylene glycol with a theoretical output weight of 0.5% of the ferric phosphate was added. The temperature was raised to 55° C. and the reaction was carried out for 2 h.

[0037] (3) adding sodium carbonate solution to the solution after the aging reaction in step (2) to adjust the pH value to 1.9, raising the temperature to 80° C., and aging the solution for 5 hours to obtain ferric phosphate dihydrate slurry; the sodium hydroxide solution was added for 30 minutes.

[0038] (4) The prepared ferric phosphate dihydrate slurry is filtered and washed with pure water at a mass ratio of 1:20 to obtain a ferric phosphate dihydrate filter cake; the filter cake is then transferred to a forced air drying oven and dried at 90°C for 10 hours to obtain ferric phosphate dihydrate; the filter cake is then loaded into an alumina sagger and sent to a high-temperature box furnace, and sintered at 450°C for 4 hours to obtain anhydrous ferric phosphate.

[0039] The anhydrous ferric phosphate prepared in Example 1 and Example 2 was analyzed by scanning electron microscope, and the results obtained are as follows: Figure 1 and Figure 2 As shown. Figure 1 and Figure 2 It can be seen that the iron phosphate prepared by the present invention is composed of particles with different particle sizes; Figure 3 From the particle size diagram, it can be seen that it constitutes a gradation of different particle sizes.

[0040] Example 3

[0041] The high-tap iron phosphate battery precursor of Example 3 is prepared by the following steps:

[0042] (1) Preparation of basic ferric phosphate: prepare 5.29 L of ferrous sulfate solution with an iron concentration of 58 g / L, 2.71 L of monoammonium phosphate solution with a phosphorus concentration of 68 g / L, and 8% hydrogen peroxide; then start the reactor to stir and heat (the reactor speed is 180 rad / min, the temperature is 40°C), pour the ferrous sulfate solution and the monoammonium phosphate solution into the reactor in turn as the base liquid, and use a peristaltic pump to drop hydrogen peroxide into the base liquid (dropping rate is 15 mL / min); after the dropwise addition is completed, the temperature is raised to 75°C, mixed and stirred for 2 hours, and filtered and washed with water to obtain a basic ammonium ferric phosphate filter cake; wherein the molar ratio of ferrous sulfate to monoammonium phosphate is 1.15:1, and the molar ratio of ferrous sulfate to hydrogen peroxide is 1:0.8.

[0043] (2) The prepared ammonium ferric phosphate filter cake was dispersed in a phosphoric acid solution with a pH value of 0.6 and stirred for 60 min until the slurry was dissolved. Then, the pH of the system was adjusted to 1.2 with a sodium hydroxide solution, and polyethylene glycol with a theoretical output weight of 0.2% of the ferric phosphate was added. The temperature was raised to 55° C. and the reaction was carried out for 1.5 h.

[0044] (3) Continue to add sodium hydroxide solution to the solution after the aging reaction in step (2) to adjust the pH value to 2.2, raise the temperature to 90° C., and age for 3 hours to obtain ferric phosphate dihydrate slurry; the sodium hydroxide solution is added for 60 minutes.

[0045] (4) The prepared ferric phosphate dihydrate slurry is filtered and washed with pure water at a mass ratio of 1:15 to obtain a ferric phosphate dihydrate filter cake; the filter cake is then transferred to a forced air drying oven and dried at 120°C for 8 hours to obtain ferric phosphate dihydrate; the filter cake is then loaded into an alumina sagger and sent to a high-temperature box furnace, and sintered at 600°C for 3 hours to obtain anhydrous ferric phosphate.

[0046] Comparative Example 1: One-step pH adjustment for aging

[0047] The comparative example 1 is substantially the same as the example 3, except that the aging is performed after adjusting the pH value by a one-step method, which specifically comprises the following steps:

[0048] (1) Preparation of basic ferric phosphate: prepare 5.29 L of ferrous sulfate solution with an iron concentration of 58 g / L, 2.71 L of monoammonium phosphate solution with a phosphorus concentration of 68 g / L, and 8% hydrogen peroxide; then start the reactor to stir and heat (the reactor speed is 180 rad / min, the temperature is 40°C), pour the ferrous sulfate solution and the monoammonium phosphate solution into the reactor in sequence as the base liquid, and use a peristaltic pump to drop hydrogen peroxide into the base liquid (dropping rate is 15 mL / min); after the dropwise addition is completed, the temperature is raised to 75°C, mixed and stirred for 2 h, and filtered and washed with water to obtain a basic ammonium ferric phosphate filter cake; wherein the molar ratio of ferrous sulfate to monoammonium phosphate is 1.15:1, and the molar ratio of ferrous sulfate to hydrogen peroxide is 1:0.8.

[0049] (2) The prepared ammonium ferric phosphate filter cake was dispersed in a phosphoric acid solution with a pH value of 0.6, stirred for 60 min until the slurry was dissolved, and then the pH of the system was adjusted to 1.8 with a sodium hydroxide solution, and the temperature was raised to 90° C. for aging reaction for 3 h.

[0050] (3) The prepared ferric phosphate dihydrate slurry is filtered and washed with pure water at a mass ratio of 1:15 to obtain a ferric phosphate dihydrate filter cake; the filter cake is then transferred to a forced air drying oven and dried at 120°C for 8 hours to obtain ferric phosphate dihydrate; the filter cake is then loaded into an alumina sagger and sent to a high-temperature box furnace, and sintered at 600°C for 3 hours to obtain anhydrous ferric phosphate.

[0051] The anhydrous ferric phosphate prepared in Comparative Example 1 was analyzed by scanning electron microscopy, and the results obtained are as follows: Figure 3 As shown. Figure 3 It can be seen that after aging using the one-step method to adjust the pH, no large-sized particles appeared, and the iron phosphate particles were uniform and of consistent size.

[0052] Comparative Example 2: One-step pH adjustment for aging + polyethylene glycol

[0053] Comparative Example 2 is substantially the same as Example 3, except that the pH value is adjusted by a one-step method and then the polyethylene glycol is used for aging, which specifically comprises the following steps:

[0054] (1) Preparation of basic ferric phosphate: prepare 5.29 L of ferrous sulfate solution with an iron concentration of 58 g / L, 2.71 L of monoammonium phosphate solution with a phosphorus concentration of 68 g / L, and 8% hydrogen peroxide; then start the reactor to stir and heat (the reactor speed is 180 rad / min, the temperature is 40°C), pour the ferrous sulfate solution and the monoammonium phosphate solution into the reactor in sequence as the base liquid, and use a peristaltic pump to drop hydrogen peroxide into the base liquid (dropping rate is 15 mL / min); after the dropwise addition is completed, the temperature is raised to 75°C, mixed and stirred for 2 h, and filtered and washed with water to obtain a basic ammonium ferric phosphate filter cake; wherein the molar ratio of ferrous sulfate to monoammonium phosphate is 1.15:1, and the molar ratio of ferrous sulfate to hydrogen peroxide is 1:0.8.

[0055] (2) The prepared ammonium ferric phosphate filter cake was dispersed in a phosphoric acid solution with a pH value of 0.6, and stirred for 60 minutes until the slurry was dissolved. Then, the pH of the system was adjusted to 1.8 with a sodium hydroxide solution, and polyethylene glycol was added. The temperature was raised to 90° C. and the reaction was aged for 3 hours.

[0056] (3) The prepared ferric phosphate dihydrate slurry is filtered and washed with pure water at a mass ratio of 1:15 to obtain a ferric phosphate dihydrate filter cake; the filter cake is then transferred to a forced air drying oven and dried at 120°C for 8 hours to obtain ferric phosphate dihydrate; the filter cake is then loaded into an alumina sagger and sent to a high-temperature box furnace, and sintered at 600°C for 3 hours to obtain anhydrous ferric phosphate.

[0057] Comparative Example 3: Adjust pH value in steps

[0058] The comparative example 3 is substantially the same as the example 3, except that the aging is performed after adjusting the pH value in steps, and specifically comprises the following steps:

[0059] (1) Preparation of basic ferric phosphate: prepare 5.29 L of ferrous sulfate solution with an iron concentration of 58 g / L, 2.71 L of monoammonium phosphate solution with a phosphorus concentration of 68 g / L, and 8% hydrogen peroxide; then start the reactor to stir and heat (the reactor speed is 180 rad / min, the temperature is 40°C), pour the ferrous sulfate solution and the monoammonium phosphate solution into the reactor in turn as the base liquid, and use a peristaltic pump to drop hydrogen peroxide into the base liquid (dropping rate is 15 mL / min); after the dropwise addition is completed, the temperature is raised to 75°C, mixed and stirred for 2 hours, and filtered and washed with water to obtain a basic ammonium ferric phosphate filter cake; wherein the molar ratio of ferrous sulfate to monoammonium phosphate is 1.15:1, and the molar ratio of ferrous sulfate to hydrogen peroxide is 1:0.8.

[0060] (2) The prepared ammonium ferric phosphate filter cake was dispersed in a phosphoric acid solution with a pH value of 0.6, stirred for 60 min until the slurry was dissolved, and then the pH of the system was adjusted to 1.2 with a sodium hydroxide solution, and the temperature was raised to 55° C. for reaction for 1.5 h.

[0061] (3) Continue to add sodium hydroxide solution to the solution after the aging reaction in step (2) to adjust the pH value to 2.2, raise the temperature to 90° C. and age for 3 hours to obtain dihydrate ferric phosphate slurry.

[0062] (4) The prepared ferric phosphate dihydrate slurry is filtered and washed with pure water at a mass ratio of 1:15 to obtain a ferric phosphate dihydrate filter cake; the filter cake is then transferred to a forced air drying oven and dried at 120°C for 8 hours to obtain ferric phosphate dihydrate; the filter cake is then loaded into an alumina sagger and sent to a high-temperature box furnace, and sintered at 600°C for 3 hours to obtain anhydrous ferric phosphate.

[0063] The performance of the iron phosphate prepared in Examples 1 to 3, Comparative Examples 1 and 3 was tested, and the results obtained are shown in Table 1 below.

[0064] Table 1 Performance of iron phosphate battery precursors of Examples 1 to 3 and Comparative Examples 1 to 3

[0065]

[0066] It can be seen from Table 1 that, compared with the one-step pH adjustment, the step-by-step pH adjustment and the one-step pH adjustment combined with the addition of polyethylene glycol, the iron phosphate battery precursor prepared by the preparation method of the present invention not only has a high tap density, but also has a large specific surface area, thereby achieving the simultaneous satisfaction of the tap density and the large specific surface area, thereby being able to improve the electrical performance of the subsequent positive electrode material prepared based on the precursor.

[0067] In addition to the above embodiments, the iron phosphate battery precursors prepared by the preparation process and preparation parameters of the present invention can achieve the technical effects claimed in the present invention. For example, during preparation, the reaction temperature after adding polyethylene glycol can be carried out under the condition of 40-60°C, the amount of polyethylene glycol added can be 0.2-1% of the theoretical output mass of iron phosphate, the aging time can be 3-6h, the aging temperature can be 75-90°C, etc., so they are not listed one by one.

Claims

1. A high-tap iron phosphate battery precursor, characterized in that: The iron phosphate is prepared by the following steps: (1) Dispersing the basic ammonium ferric phosphate filter cake in an acid solution with a pH value of 0.4 to 0.6, stirring for 30 to 60 minutes until the filter cake is completely dissolved, adding alkali solution to adjust the pH value of the base solution to 0.8 to 1.2, and adding polyethylene glycol, and reacting at 40 to 60° C. for 1 to 2 hours; (2) adding alkali solution to the solution after the reaction in step (1) to adjust the pH value to 1.8-2.2, raising the temperature to the aging temperature, and aging for 3-6 hours to obtain ferric phosphate dihydrate slurry; (3) The dihydrate iron phosphate slurry is filtered, washed, dried, and calcined to obtain anhydrous iron phosphate with high tap density.

2. The high-tap iron phosphate battery precursor according to claim 1, characterized in that: In step (1), the amount of polyethylene glycol added is 0.2-1% of the theoretical output mass of ferric phosphate.

3. The high-tap iron phosphate battery precursor according to claim 1, characterized in that: In step (2), the alkali solution is added for 30 to 60 minutes, and the aging temperature is 75 to 90°C.

4. The high-tap iron phosphate battery precursor according to claim 1, characterized in that: In step (1), the basic ammonium ferric phosphate filter cake is prepared by the following steps: preparing a ferrous salt solution, a phosphate salt solution, and an oxidant, mixing and stirring, and filtering and washing with water to obtain a basic ammonium ferric phosphate filter cake; wherein the molar ratio of the ferrous salt to the phosphate salt is (1 to 1.15):1, and the molar ratio of the ferrous salt to the oxidant is 1:(0.5 to 0.8).

5. The high-tap iron phosphate battery precursor according to claim 4, characterized in that: The iron concentration of the ferrous salt solution is 55-58 g / L, and the ferrous salt is ferrous sulfate and / or ferrous chloride.

6. The high-tap iron phosphate battery precursor according to claim 4, characterized in that: The phosphorus concentration of the phosphate salt solution is 65-68 g / L, the phosphate salt is monoammonium phosphate and / or diammonium phosphate; and the oxidant is hydrogen peroxide and / or sodium peroxide.

7. The high-tap iron phosphate battery precursor according to claim 4, characterized in that: The acid solution includes at least one of phosphoric acid, sulfuric acid or hydrochloric acid; the alkali solution includes at least one of sodium hydroxide, sodium carbonate or sodium bicarbonate.

8. The high-tap iron phosphate battery precursor according to claim 1, characterized in that: In step (3), the mass ratio of ferric phosphate dihydrate to pure water during the suction filtration and water washing is 1:(15-25); the drying temperature is 90-120° C., and the drying time is 8-12 hours; the calcination temperature is 450-600° C., and the calcination time is 2-4 hours.

Citation Information

Cited By

  • Synthesis method of battery-grade iron phosphate

    CN120793868A